2011
DOI: 10.1007/978-3-642-18272-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Major Feedback Loops Supporting Artificial Evolution in Multi-modular Robotics

Abstract: In multi-modular reconfigurable robotics it is extremely challenging to develop control software that is able to generate robust but still flexible behavior of the 'robotic organism' that is formed by several independent robotic modules. We propose artificial evolution and self-organization as methodologies to develop such control software. In this article, we present our concept to evolve a self-organized multimodular robot. We decompose the network of feedbacks, that affect the evolutionary pathway and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, we demonstrated that AHHS controllers can be implemented on real robotic hardware, and also robots with low computational capabilities (like the e-puck robot) can be controlled by these controllers. Although this article reports only an exemplary case study on robotic hardware, it gives justified hope that more complex behaviors can be generated on robots with these methods (see [7]). This will be done by successively adding new sensors to the system, which secret additional virtual hormones and interact with the basic driving and collision avoidance system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we demonstrated that AHHS controllers can be implemented on real robotic hardware, and also robots with low computational capabilities (like the e-puck robot) can be controlled by these controllers. Although this article reports only an exemplary case study on robotic hardware, it gives justified hope that more complex behaviors can be generated on robots with these methods (see [7]). This will be done by successively adding new sensors to the system, which secret additional virtual hormones and interact with the basic driving and collision avoidance system.…”
Section: Discussionmentioning
confidence: 99%
“…Then we will implement more complex AHHS on robotic hardware. One significant extension will be the application of AHHS to swarm robots and on multi-modular robotic systems [7]. In such systems AHHS will be a very interesting control paradigm, as inter-robotic communication will be implemented similar to sensor-induced hormone secretion, thus, mimicking the step from uni-cellular organisms to multi-cellular lifeforms.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of causes and effects define a loop (called feedback loop). Feedback loops have already been used in the context of MAS, for example, for applications such as manufacturing, collective robotics, simulation and information systems design (Brückener, 2000;Wolf and Holvoet, 2007;Caprarescu et al, 2009;Beurier et al, 2003;Schmickl et al, 2011).…”
Section: Introductionmentioning
confidence: 98%